Challenges and Opportunities of Women Entrepreneurs - With Special Reference to MSMES in the State of Karnataka - Dr. S. Poornima, (International Journal of Engineering and Management Research, 2024)
The present article aims at discussing the challenges and opportunities of women entrepreneurs of MSMEs sector in Karnataka state. Primary data was collected with the help of structured questionnaire and collected the information from the selected women entrepreneurs of MSMEs from the Karnataka state. In the present study, the researcher used simple percentage analysis. The researcher discussed and analyzed the financial, personal, social, labour, marketing, infrastructural and technological problems faced by the women entrepreneurs. In this article the researcher also discuss about the opportunities of women entrepreneurs at national and state level.